Direct preparation of standard functional interfaces in oxide heterostructures for 2DEG analysis through beam-induced platinum contacts - Amoresi, Rafael A. C. [UNESP]; Cichetto, Leonélio; Kundu, Swarup [UNESP]; Teodoro, Marcio D.; Marques, Gilmar E.; Longo, Elson; Andrés, Juan; Chiquito, Adenilson J.; Zaghete, Maria A. [UNESP] (AIP Publishing, 2018)
Two-dimensional electron gas (2DEG) in SrTiO3/LaAlO3 heterostructures has been extensively studied in the last few years; however, little attention has been given to a practical way to contact electrically the low dimensional gas at the interface. This work demonstrates a method to contact the 2DEG formed at the oxide interfaces connected by platinum electrodes which were made by the decomposition of organometallic gas using focused ion beams. On the surface, the electrodes were defined through photolithography, and at the interface, the electrodes were deposited through the focused ion beams and electrons, which were then evaluated. The quality of the interface electrodes was evaluated at two different partial oxygen pressures (pO2) used for the film deposition: low (10−4 mbar) and high (10−1 mbar). The electrode deposition conditions using electrons or ions have resulted in different rates of metal deposition and interaction with the interface leading to either metallic (2DEG) or insulating behavior.